Simplify -3xy3 + 7xy3 + (-xy3) + (-3xy3)

Question

Asked 4/18/2011 12:42:47 PM

Updated 5/25/2014 4:39:10 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [5/25/2014 4:38:36 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Expert answered|Ashm45315|Points 0|

Question

Asked 4/18/2011 12:42:47 PM

Updated 5/25/2014 4:39:10 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by alfred123 [5/25/2014 4:38:36 PM]

Rating

8

-3xy^3 + 7xy^3 + (-xy^3) + (-3xy^3)

-3xy^3 + 7xy^3 -xy^3 -3xy^3

= 0

-3xy^3 + 7xy^3 -xy^3 -3xy^3

= 0

Added 5/25/2014 4:38:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 4:45:13 PM]

8

(5b)(-3a) = -15ab

Added 5/25/2014 4:39:10 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/25/2014 4:45:23 PM]

simplify |x| - |-x| **Weegy:** |x| - |-x| = 0 **User:** Simplify 7(A - 6) **Weegy:** 7(A - 6)= 7A - 42 **User:** Simplify 7(A - 6) **Weegy:** 7(A - 6)= 7A - 42
(More)

Question

Expert Answered

Updated 3/5/2014 2:18:18 AM

0 Answers/Comments

Simplify -2[9 - (x + 7)] **Weegy:** 5 (x -2) - 3( x - 4) = 10. In expanded form 2x+2=10. The answer x= 4. Click on the "Good" button. Thank you. (More)

Question

Updated 3/28/2015 8:44:58 AM

1 Answer/Comment

-2[9 - (x + 7)]

= -2[9 - x - 7]

= -2[2 - x]

= -4 + 2x

= -2[9 - x - 7]

= -2[2 - x]

= -4 + 2x

Added 3/28/2015 8:44:55 AM

This answer has been confirmed as correct and helpful.

Which of the following expressions is equivalent to 6m - 10?
A. 2(3m + 5)
B. -2(5 - 3m)
C. 2(3m - 10)

Question

Expert Answered

Updated 3/5/2014 2:28:11 AM

0 Answers/Comments

t Object]User: Simplify 10 + 4(x + 1) + 5 **Weegy:** 10 + 4(x + 1) + 5, 10 + 4x + 4 + 5= 4x + 19 **User:** Simplify 5(MN + 1) - 5 **Weegy:** 5(MN + 1) - 5 = 5MN **User:** Simplify 7(x + 2) + 12 **Weegy:** 7(x + 2) + 12 = 7x+26 **User:** Simplify 7(B + 3) + 2B (More)

Question

Expert Answered

Updated 3/5/2014 2:20:37 AM

1 Answer/Comment

7(B + 3) + 2B

7B + 21 + 2B

= 9B + 21

7B + 21 + 2B

= 9B + 21

Added 3/5/2014 2:20:37 AM

This answer has been confirmed as correct and helpful.

|-11| + |-7| **Weegy:** 18.PLEASE CLICK gOOD **User:** simplify 5m - 13n - n + 4m **Weegy:** m-14n **User:** Simplify -|-5 + 2| **Weegy:** 7 (More)

Question

Expert Answered

Updated 3/21/2014 9:20:39 AM

3 Answers/Comments

|-11| + |-7|

= 18

= 18

Added 3/21/2014 9:19:26 AM

This answer has been confirmed as correct and helpful.

5m - 13n - n + 4m

= 9m - 14n

= 9m - 14n

Added 3/21/2014 9:19:54 AM

This answer has been confirmed as correct and helpful.

-|-5 + 2|

5 - 2

= 3

5 - 2

= 3

Added 3/21/2014 9:20:39 AM

This answer has been confirmed as correct and helpful.

36,646,645

questions answered

There are no comments.